Lukenda proti Sloveniji - Rus, Mateja (Revus (Ljubljana), 2005)
European Court of Human rights held in case Lukenda v. Slovenia that there had been a violation of the Article 6 which guarantees the right to the hearing within a reasonable time and also that there had been a violation of the Article 13 which guarantees the right to an effective remedy for an alleged breach of the requirements under the Article 6. Furthermore, the Court found that the violation of the applicant's right was not an isolated incident, but a systemic problem that has originated in the malfunctioning of domestic legislation and practice. All Government's preliminary objections claiming non-exhaustion of adequate and effective domestic remedies were dismissed by the Court. Upon the Court's opinion the domestic remedies separately (namely action in the administrative courts, tort claim, request for supervision and constitutional appeal) or the aggregate cannot amount to an effective legal remedy. As the Government failed to establish the effectiveness of domestic remedies, the Court held unanimously, that there had been a violation of the Article 13. Moreover, in the Court's view, the overall length of the proceedings in the applicant's case was excessive and failed to meet the "reasonable-time" requirement, so therefore a breach of the Article 6 was established. In conclusion, the Court did not only award just satisfaction to the applicant, but also "suggested" Slovenia to adopt appropriate general and individual measures in order to put an end to the violation found by the Court or to redress as far as possible its effects.
Keywords: človekove pravice; Evropsko sodišče za človekove pravice; pravica do sojenja v razumnem roku; sodišča; sodna praksa